A problematização da docência universitária no contexto do capitalismo universitário - Rodrigues, Eliana Curvelo [UNESP]; Grego, Sonia Maria Duarte [UNESP]; Romanatto, Maria José [UNESP] (My University, 2010)
The university environment is in metamorphosis, in a possibility of its recreation in the presence of a knowledge revolution at full XXI century. Its structure, based at a science model, presents itself undermined by not breaking the stagnation in a world that inaugurates boundaries of uncertainty for all humanity participants. From that perception, this work intend to understand how the globalization has been reduced the workforce of the university teacher. Moreover, how the hegemonic groups, derived from insertion of capitalism and globalization, root themselves in the academic environment – before considered a space of autonomy – is transforming the teaching profession through mechanisms of alienation and doctrinairism that disseminate the heteronomy as alternative for maintenance of dogmas and, therefore, certainties.

O meio acadêmico universitário encontra-se em metamorfose, na possibilidade de sua recriação perante a revolução do conhecimento em pleno século XXI. Sua estrutura, fundamentada por um modelo de ciência, apresenta-se fragilizada por não romper a estagnação em um mundo que inaugura fronteiras de incertezas para todos os partícipes da humanidade. Decorrente dessa percepção, o presente texto procurará entender como a globalização fragiliza a força de trabalho do docente universitário. Além disso, como o domínio dos grupos hegemônicos derivados da inserção do capitalismo e da globalização enfeudaram-se no meio acadêmico – antes tido como espaço de autonomia, vem transformando o trabalho docente por meio de mecanismos de alienação e doutrinação que disseminam a heteronomia como alternativa para a manutenção de dogmas e, portanto, de certezas.
The problem of the university teaching in the university capitalism context
Keywords: Higher education; Globalization; Academic capitalism; Teaching profession; Educação superior; Globalização; Capitalismo acadêmico; Docência; Trabalho docente